1982
DOI: 10.1073/pnas.79.5.1453
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential changes induced by the ouabain-like compound extracted from mammalian brain.

Abstract: The electrical membrane potential (All) of chicken embryo fibroblasts in tissue culture was determined to be -30.5 ± 2.9 mV as measured by distribution of the lipophilic [3H]tetraphenylphosphonium cation (Ph4P+). Stimulation of the electrogenic activity of the Na+,K+-ATPase by the ionophore monensin induces a hyperpolarization of -47 mV and a new At of -77.3 ± 5.7 mV. The effects of the cardiac glycoside ouabain and an "ouabain-like compound" (OLC), which was extracted and partially purified from sheep brain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In addition, the extract inhibited ouabain binding to frog urinary bladder. Similarly, an endogenous compound which -with re spect to ouabain -competitively bound to erythrocytes was isolated from mammalian brain tissue [21]. More recently, Gruberetal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extract inhibited ouabain binding to frog urinary bladder. Similarly, an endogenous compound which -with re spect to ouabain -competitively bound to erythrocytes was isolated from mammalian brain tissue [21]. More recently, Gruberetal.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of K π (or gain of Na π ) produced by K π -(or Na π -) selective ionophores is counterbalanced by an equivalent molar gain of Na π (or loss of K π ), such that the end result is that normal Na π and K π gradients are partially abolished (Feinstein et al 1977). Increased intracellular Na π levels activate the Na π -K π pump (Smith & Rozengurt 1978;Lichtshtein et al 1979;Brodie et al 1987) and the Na π -Ca ππ exchanger in the reverse mode (Barcenas-Ruiz et al 1987;Ambroz et al 1990) resulting in increased cytoplasmic Ca ππ levels and the stimulation of K Ca currents (Lichtshtein & Samuelov 1982;Mason & Grinstein 1990). Both pump activation and the stimulation of K Ca currents result in membrane hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxylic ionophore-induced hyperpolarization is not limited to neurones and has also been demonstrated in a variety of cellular models (Smith & Rozengurt 1978;Alonso & Carrasco 1982;Seeman et al 1983;Yada & Okada 1984;Ozawa 1985;Brodie et al 1987;Mason & Grinstein 1990). This hyperpolarization is believed to arise from secondary consequences of induced transport activity, involving stimulation of the Na π -K π pump (Smith & Rozengurt 1978;Alonso & Carrasco 1982;Brodie et al 1987) and/or Ca ππ -dependent K π currents (K Ca ; Lichtshtein & Samuelov 1982;Mason & Grinstein 1990).…”
mentioning
confidence: 99%
“…One exception is that of De Pover et al , 43 who extracted inhibitory activity from guinea pig heart. On the other hand, Alaghband-Zadeh et al, 4 * using an indirect assay of Na + ,K + -ATPase activity, processed numerous organ tissues from the rat (including cerebral cortex tissue) and found inhibitory activity only in extracts from the hypothalamus.…”
Section: Extracts From Tissuementioning
confidence: 99%
“…Material prepared from sheep brain by the same procedure influenced electrical membrane potential in chick embryo fibroblasts in a manner parallel to that of ouabain. 43 This brain fraction was further purified by HPLC and shown to exert positive inotropic effects in sheep cardiac muscle. 26 Preliminary characterization efforts suggested that the material was a low-molecular-weight, polar, nonpeptidic molecule, in agreement with the findings of Haupert and Sancho.…”
Section: Extracts From Tissuementioning
confidence: 99%